PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS PERMAINAN EDUKASI WORD WALL PADA MATERI PECAHAN UNTUK SISWA SEKOLAH DASAR - Julaika; Yusuf, Munir; Munawir, Ahmad (An-Nahdlah: Jurnal Pendidikan Islam, 2024)
This research aims to determine the analysis of the need for developing interactive learning media based on word wall educational games on fraction material in class IV at SDN 173 Kertoraharjo, Kec. East Tomoni, Kab. East Luwu. This research uses Research & Development (R&D) research with the ADDIE development model which consists of 5 stages, namely the analysis stage, design stage, development stage, implementation stage and evaluation stage. This research was carried out at SDN 173 Kertoraharjo with the subjects in this research being the class IV homeroom teacher and 19 class IV students. Meanwhile, the object of this research is interactive media based on word wall educational games on fraction material. Then the techniques used in data collection are interviews, questionnaires, tests and documentation. As well as data analysis techniques using qualitative data analysis and quantitative data analysis. The results of this development research show that students need an interesting learning media on fraction material such as interactive learning media based on word wall educational games on fraction material. The implication of this development research is that learning can be interesting, increase student learning motivation and student learning outcomes can increase.